Citogenética e cultivo in vitro de espécies e híbridos de Passiflora L. - Coelho, Maria do Socorro Evangelista (2015)
Brazil is one of the main centers of genetic diversity and dispersion of the genus Passiflora. In the present work, several species and interspecific hybrids of Passiflora were characterized through cytogenetic techniques and ISSR markers, as well as these genotypes were evaluated for in vitro multiplication and establishment. Chromosomal preparations were submitted to conventional staining, CMA3/DAPI banding, FISH using 45S/5S rDNA probes and GISH. Genomic DNA of P. edulis and P. cincinnata were used as genomic probes in the GISH. Twenty ISSR primers were used for the characterization by molecular markers. Nodal segments of P. cincinnata, P. laurifolia, P. setacea and P. luetzelburgii were collected and evaluated in the WPM, DKM and MS culture media to establishment of in vitro culture; for in vitro multiplication, explants were inoculated in DKW culture media under different concentrations of BAP, KIN and 2iP cytokinins. The results showed 2n = 18 chromosomes for the species and hybrids, regular meiosis, one pair of 5S rDNA sites and two or three pairs of 45S rDNA sites co-localized with the CMA3+/DAPI- bands. It is the first chromosomal counting recorded for P. luetzelburgii. Three groups distinct of chromosomes were revealed by GISH. The hybrid origin and the relationship with the parental species were also confirmed by using of the ISSR markers. DKW culture medium provided the better development of the explants, P. cincinnata CPE16 showed the better in vitro morphogenetic response, and KIN showed to be more efficient in obtaining increased shoots length.